2018
DOI: 10.4000/geomorphologie.11927
|View full text |Cite
|
Sign up to set email alerts
|

Efficacité et résistance de techniques de protection de berges en génie végétal

Abstract: Un ensemble de dix-neuf ouvrages de protection de berges en génie végétal a fait l' objet d'un suivi à court et long termes sur plusieurs rivières de Wallonie. Les aménagements, dont la mise en place remonte pour certains à 20 ans, ont dans l' ensemble bien rempli leur rôle de stabilisation de berge, même si plusieurs d' entre eux sont aujourd'hui partiellement détruits. Dans certains cas, l' endommagement des aménagements a conduit à une reprise de l' érosion de la berge à protéger. Le facteur principal de dé… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…This result is consistent with Watson et al [1997], who found that a Rc/W value of 2 could be a lower limit for willow post soil bioengineering structures. Note that the bend curvature was also observed to be critical for other soil bioengineering structures such as combs [Peeters et al, 2018], which suggests that the explanation driving this process should be sought elsewhere.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This result is consistent with Watson et al [1997], who found that a Rc/W value of 2 could be a lower limit for willow post soil bioengineering structures. Note that the bend curvature was also observed to be critical for other soil bioengineering structures such as combs [Peeters et al, 2018], which suggests that the explanation driving this process should be sought elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…To finish, surrogates are often used to simulate in a more or less realistic manner some of the components of the problem studied [Maike et al, 2016]. Here we used nylon threads to simulate the use of anti-scouring twigs (Figure 3), a promising and soft solution sometimes encountered in the field [Peeters et al, 2018]. The difficulty of course is to ensure a realistic stiffness of the surrogate.…”
Section: Scalingmentioning
confidence: 99%
See 3 more Smart Citations